Analisis Pengaruh Kompetensi Terhadap Kinerja Customer Complaint Handling Dengan Komitmen Organisasi Sebagai Variabel Moderasi (Studi Pada PT. Pos Indonesia Persero Kantor Regional 7 Jawa Timur 60004) - Jumadi, Jumadi; Santoso, Rahmat Agus; Sukaris, Sukaris (Jurnal Maksipreneur, 2023)
The business continuity of a company is supported by the level of achievement of performance targets that have been set. This study aims to determine the influence of oragnization commitment, employee competence, and the role of organizational commitment moderation in influencing competence on customer complaint handling (CCH) performance at Regional Office 7 East Java Surabaya 60004. The population is all customer service employees at PT Pos Indonesia (Persero) which amounts to 130 people. Sampling uses the total sample method, which is the entire population. This research uses a quantitative approach using deductive methods. The data analysis technique used is the Moderated Regression Analysis (MRA) method using the SPSS For Windows program. The results of this study found that partially the competence and commitment of the organization had a significant positive effect on CCH's performance at PT Pos Indonesia (Persero) Regional Office 7 East Java 60004. In addition, it was found that the organization's commitment was able to moderate the positive influence of competence on CCH performance at PT Pos Indonesia (Persero) Regional Office 7 East Java 60004.